The Mean Free Path of Wave-Particle Interactions in Astrophysical Plasmas - Héctor Pérez-de-Tejada (Scientific Research, New Technologies and Applications Vol. 10, 2024)
Dissipation processes derived from the kinetic theory of gases (shear viscosity and heat conduction) are employed to examine the solar wind that interacts with planetary ionospheres. The Larmor radius of the planetary particles can be comparable to a planetary radius (Venus–Mars), and thus they may be subject to laminar motion in large distances along the planetary wakes. Since particle–particle interactions under such conditions are practically non-existent in the solar wind–planet interaction region, it is necessary to consider that other processes should be effective to produce the measured stochastic motion of the plasma particles. The purpose of this study is to estimate the mean free path of wave-particle interactions that produce a continuum response in plasma behavior. Wave-particle interactions are necessary to support the fluid dynamic interpretation that accounts for various features measured in a solar wind–planet ionosphere region; namely, (i) the transport of solar wind momentum to an upper ionosphere in the presence of a velocity shear, and (ii) plasma heating produced by momentum transport. From measurements conducted in the solar wind interaction with the Venus ionosphere, it is possible to estimate that in general terms, the mean free path of wave-particle interactions reaches \(^γH 1000 \) km values that are comparable to the gyration radius of the solar wind particles in their Larmor motion within the local solar wind magnetic field. Similar values are also applicable to conditions measured by the Mars ionosphere and in cometary plasma wakes. Considerations are made in regard to the stochastic trajectories of the plasma particles that have been implied from the measurements made in planetary environments. At the same time, it is possible that the same phenomenon is applicable to the interaction of stellar winds with the ionosphere of exoplanets, and also in regions where streaming ionized gases reach objects that are subject to rotational motion in other astrophysical problems (galactic flow–plasma interactions, black holes, etc.). A useful outcome in the onset of wave-particle interactions for the solar wind that mixes up with planetary/cometary plasmas is that similar conditions should also be applicable in the interaction of stellar winds with exoplanets. In such cases, there should also be evidence of a fluid dynamic response in the behavior of the interacting plasmas. Similarly, it would be of interest to examine whether a fluid dynamic approach is also applicable to galactic-scale interactions of plasma-directed flows mixing with rotating plasmas.